Child Safety Monitoring System - Najwa Hannan , Mohd Subri (UTeM, 2009)
The idea of this project comes out because of when the house become larger, more risky and dangerous to children. A child safety monitoring system detected when a child enters a dangerous area at home. The main objective of this system is to help avoid child injuries. This system contains of three parts of circuits which are sensor circuit, RF wireless transmitter and receiver circuit, and LCD display circuit. Infrared sensors are embedded into a doorway to monitor activity so that the device can distinguish between the presence of an adult and a child. When child cross through the doorway, the output can be displayed on the LCD display to alert the parents of danger. The output display is corresponded to a chosen position setting, for example bathroom and kitchen. The devices are tested for accuracy and reliability.